Inventory Behavior and Financial Constraints: Theory and Evidence - Dasgupta, Sudipto; Li, Erica X N; Yan, Dong (Review of Financial Studies, 2019)
We model the interaction of financial constraints, capacity constraints, and the response of production and inventory to cost and demand shocks. The model predicts that in response to favorable shocks, financially constrained firms are unable to build inventory as rapidly as are unconstrained firms. However, because the favorable shocks gradually ease the financial constraints, constrained firms continue to build inventory and eventually carry surplus inventory (relative to unconstrained firms) to unfavorable states. This allows them to deplete inventory more aggressively in response to unfavorable shocks. Our empirical evidence provides broad support for the model’s predictions.Received September 3, 2016; editorial decision January 11, 2018 by Editor David Denis. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.